Climbing Fitz Roy, 1968 Reflections on the Lost Photos of the Third Ascent - Chouinard, Yvon 1938- (Patagonia, 2013)
This book features rare, once-thought-lost photos of the 1968 first ascent of the California Route on Cerro Fitz Roy, the third ascent of the mountain. With accompanying retrospective essays. Climbing Fitz Roy,1968, presents photo documentation of the climb, places it in the social and climbing context of the times, and reflects how this momentous trip influenced the lives of those involved, and in a greater context, the lives of so many others.
Keywords: Mountaineering -- Argentina; Mountaineering expeditions -- Argentina; Mountains -- Difficulty of ascent; Electronic books